Assessing the Influence of Corporate Governance Principles on Disclosure and Financial Report Quality: Evidence from Saudi Listed Companies - Albalwy, Hanan Rashid (Journal of Economic, Administrative and Legal Sciences, 2025)
This study explores the impact of corporate governance rules on disclosure and the quality of financial reports in Saudi listed companies. The researcher employed a descriptive analytical method, collecting data from 90 board members and executives of Saudi listed companies in the 2024 through a survey. Data analysis, conducted using SPSS, revealed that the implementation of governance rules significantly enhanced disclosure levels and improved the quality of financial reports. Moreover, fostering a governance culture positively impacted the sustainability of companies and strengthened their position in the financial market, supporting their long-term goals. The study emphasized the importance of a professional and credible organizational and managerial structure to ensure the effective application of governance principles. It recommended reinforcing the concepts and adherence to rules set by the Organisation for Economic Co-operation and Development (OECD) through training programs. The study also called for the establishment of a specialized committee to monitor the implementation of governance principles and ensure corporate compliance. Additionally, it stressed the need to broaden the dissemination of governance culture among all stakeholders by providing guidelines and publications, contributing to the enhancement of governance principles within the financial community and improving disclosure quality for companies listed in the Saudi financial market.